126k views
4 votes
Which expression is equal to (In picture)

Which expression is equal to (In picture)-example-1

2 Answers

3 votes


3x^2+12x-15=3(x^2+4x-5)=3(x^2+5x-x-5)\\\\=3[x(x+5)-1(x+5)]=3(x+5)(x-1)\\----------------------\\4x^2+4x-8=4(x^2+x-2)=4(x^2+2x-x-2)\\\\=4[x(x+2)-1(x+2)]=4(x+2)(x-1)\\----------------------\\2x^2-8=2(x^2-4)=2(x^2-2^2)=2(x-2)(x+2)\\----------------------\\x^2-5x=x(x-5)\\----------------------\\\\(3x^2+12x-15)/(4x^2+4x-8)\cdot(2x^2-8)/(x^2-5x)\\\\=(3(x+5)(x-1))/(4\!\!\!\!\diagup_2(x+2)(x-1))\cdot(2\!\!\!\!\diagup^1(x-2)(x+2))/(x(x-5))\\\\\text{Canceled:}\ (x-1)\ \text{and}\ (x+2)


=\boxed{(3(x-2)(x+5))/(2x(x-5))}

User Aranxo
by
6.0k points
6 votes
The last answer, factorise first then cancel the ones that has the same expression ☺
Which expression is equal to (In picture)-example-1
User Rfeak
by
5.3k points